Apontamentos sobre a construção sócio-histórica de estigmas e estereótipos em relação ao homoerotismo entre mulheres - Toledo, Lívia Gonsalves [UNESP]; Teixeira Filho, Fernando Silva [UNESP] (My University, 2011)
This article aims at to count the history about the homoerotism among women in the western societies and in the modernity seeking to notice what bases stigmata and stereotypes on lesbianity at the present time. For that, it was collected in scientific works about feminine sexuality and homosexuality information regarding the lesbianity theme – scarce and of difficult access. The macho system and the phallocentrism put a mantle on that history, making it invizibilizated and ilegitimated. Removing the lesbianity from the obscurantism could contribute to the reflection on public policy issues that pertain to lesbian women and with homoerotic relationships and practices and contribute for the production of life quality for people that are moved by binary perspectives of stigmata and stereotypes. That research was financed by Fundação de Amparo à Pesquisa do Estado de São Paulo – FAPESP, and accomplished by the PósGraduation Program of the Universidade Estadual Paulista – Campus of Assis SP.

Esse artigo objetiva contar a história sobre o homoerotismo entre mulheres nas sociedades ocidentais e na modernidade visando perceber o que embasa estigmas e estereótipos sobre a lesbianidade na atualidade. Para isso, coletou-se em trabalhos científicos sobre a sexualidade feminina e a homossexualidade informações referentes à temática da lesbianidade – escassa e de difícil acesso. O machismo e o falocentrismo colocaram um manto sobre essa história, fazendo-a invizibilizada e ilegitimada. Tirando a lesbianidade do obscurantismo, possibilita-se problematizações psicossociais que podem contribuir para a produção de qualidade de vida para pessoas que são movidas por perspectivas binárias de estigmas e estereótipos. Esse estudo foi financiado pela FAPESP – Fundação de Amparo à Pesquisa do Estado de São Paulo, e é parte da dissertação de mestrado da autora, realizado junto ao Programa de PósGraduação em Psicologia da Universidade Estadual Paulista Júlio de Mesquita Filho – Campus de Assis-SP.
Notes about the socio-historical construction of stigmas and stereotypes in relation to homoerotism among women
Keywords: Lesbianity; Homoerotism; History; Stigmas; Stereotypes; Lesbianidade; Homoerotismo; História; Estigmas; Estereótipos